2018
DOI: 10.1016/j.jconrel.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Anti-polyethylene glycol antibodies alter the protein corona deposited on nanoparticles and the physiological pathways regulating their fate in vivo

Abstract: Multiple studies highlight the strong prevalence of anti-poly(ethylene glycol) (anti-PEG) antibodies in the general human population. As we develop therapeutic modalities using this polymer, it is increasingly relevant to assess the importance of anti-PEG antibodies on biological performances. Here, we show that the anti-PEG Immunoglobulin M (IgM) raised in mice following the injection of polymeric nanoparticles could have significant neutralizing effects on subsequent doses of PEGylated nanosystems in vivo. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 53 publications
3
75
0
Order By: Relevance
“…However, the mechanism of clearance dependent on the presence of anti-PEG antibody is only partially understood. A recent study by Grenier et al (2018) focused on the clearance rate of different PEGylated molecules, such as PLGA NPs, liposomes, and BSA, which demonstrated how even a single administration of PEG-PLGA NPs could induce the production of anti-PEG IgM and increase NP clearance by their activation of the complement system through the classical pathway. This not only reduced the circulation time of PEG-PLGA NPs after a second administration but also induced cross-reaction toward PEGylated liposomes, increasing also their clearance.…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…However, the mechanism of clearance dependent on the presence of anti-PEG antibody is only partially understood. A recent study by Grenier et al (2018) focused on the clearance rate of different PEGylated molecules, such as PLGA NPs, liposomes, and BSA, which demonstrated how even a single administration of PEG-PLGA NPs could induce the production of anti-PEG IgM and increase NP clearance by their activation of the complement system through the classical pathway. This not only reduced the circulation time of PEG-PLGA NPs after a second administration but also induced cross-reaction toward PEGylated liposomes, increasing also their clearance.…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…Engineered nanoparticles (NPs) for biomedical applications undergo spontaneous protein adhesion when placed in biological fluids, such as blood. This phenomenon is known as protein corona [ 1 ] and it has direct implications in the cellular uptake, [ 2 ] circulating times, [ 3 ] fate, [ 4 ] and toxicity [ 5 ] of NPs in living beings. Thus, in order to learn about the NPs' interaction with proteins and cells, in situ characterization would be helpful, that is, quantification methods without the need to isolate NPs from their environment.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-existing anti-PEG antibodies have also been linked to allergic reactions after the infusion of pegylated medicines [29,31]. However, other studies have reported that anti-PEG IgM cannot accelerate the clearance of pegylated proteins [37]. Taken together, there is a need to investigate the effects of anti-PEG antibodies on pegylated drugs.…”
Section: Introductionmentioning
confidence: 99%